A demographic test of accidental versus intentional island colonization by Pleistocene humans. Issue 145 (August 2020) - Ihara, Yasuo; Ikeya, Kazunobu; Nobayashi, Atsushi; Kaifu, Yosuke
Abstract: This study evaluates the hypothesis that some documented cases of long-distance sea crossing by the Late Pleistocene Homo sapiens occurred as a result of accidental drifting, rather than by intentional seafaring. For that purpose, we use an existing computer simulation framework, with some modifications, to investigate the likelihood that a planned or unplanned island colonization by a small group of individuals will persist to establish a viable population. Within the original framework, planned colonization was operationally characterized as being initiated by equal numbers of unrelated young men and women, whereas for unplanned colonization, those who migrate inadvertently were regarded in effect as a random sample of the whole population. Here, we consider a different scenario for unplanned colonization, which we believe is more relevant to sea crossing by the Late Pleistocene humans, that is, we assume that unplanned colonization occurs when members of households on watercrafts with limited voyaging capabilities are drifted away by ocean currents and washed up on a distant island. We also extend the previous analysis by considering a broader range of combinations of fertility and mortality schedules that individuals are assumed to follow. Our simulations suggest the following: (1) colonization of an island by ten or fewer unrelated young men and women can be successful within the feasible range of fertility and mortality levels; (2) in comparison, the likelihood of success for unplanned colonization is considerably smaller for the same range of fertility and mortality levels; and (3) there exists a small range of parameter combinations for which unplanned colonization has a non-negligible prospect of success even without assuming recurrent accidental drifts to the same island, and thus, the accidental colonization scenario cannot be totally excluded. In addition, we find that the minimum founding population required for successful colonization varies substantially depending on the fertility and mortality levels. Highlights: Demographic aspects of human island colonization in the Late Pleistocene are examined. Under ideal conditions, ten or fewer founders may suffice for successful colonization. Colonization as a result of accidental drifting is considerably less plausible. The accidental colonization hypothesis nevertheless cannot be totally excluded.